Border Extraterritoriality or Cosmopolitan Responsibility? Conceptualizing the Possibility of Asylum Claims in absentia - Tyler Correia (Studies in Social Justice)
An emergent issue for critical migration studies concerns the technological and diplomatic capacities of Western nation-states to externalize bordering practices. The extraterritorialization of border enforcement presents a dual problematic for migrants, intellectuals, activists, and civil-society members. They must navigate, on one hand, a pressing need to respond to the pre-emptive foreclosure of a “right to presence,” while on the other hand rethinking institutions of asylum to be capable of operating from a distance. In the following, I construct a new manner of thinking about border extraterritorialization in general, and in response, formulate rightful claims to asylum as articulated in absentia. Extraterritorialization practices and their logics are characterized by pro-jection, through which they give rise to a “general domain of ends” predicated on nation-state irresponsibility, outside of law and outside of their territories. I then elaborate upon a notion of cosmopolitanism that characterizes grassroots actions attempting to address these bordering practices, ones that challenge state-centric frameworks of politics. In advancement of this position, I discuss how a relation of responsibility may be constructed from a distance through civil society initiatives (private sponsorship), counter-public networks (exemplified by WatchTheMed), and counter-institutions (the International Parliament of Writers). All these examples represent a form of communicative reach.